Efektivitas Pelaksanaan Tugas Dan Fungsi Bagian Humas Dan Protokol Dalam Menjaga Citra Kepala Daerah Pada Humas Dan Protokol Sekretariat Daerah Kabupaten Jembrana - I Gede Arya Suta Satya Pramana; Ni Wayan Sutiani (Universitas Mahendradatta Denpasar, 2020)
Every government agency, company, or other institution must have a PublicRelations and Protocol. Public Relations and Protocols have the duty and function totake responsibility and maintain a positive image that already exists in an agency orcompany and to better re-image where the agency or company is located, has the roleof delivering a policy or all information carried out by an agency or a company. Fromthe above background, the purpose of this study is to find out how the effectivenessof the implementation of the duties and functions of the Public Relations and ProtocolSection in Maintaining the Image of the Regional Head (Study in the Public Relationsand Protocol Section of the Jembrana Regency Regional Secretariat.The data in thisstudy are qualitative secondary data. The population was taken from employees in thePublic Relations and Protocol Section of the District Secretariat of Jembrana totaling35, the sample method used was the census method. The data analysis technique usedis descriptive qualitative analysis. Data collection methods used in this research areinterview and documentation study methods.The results of the study showed that theeffectiveness of the duties and functions of the Public Relations and Protocol sectionin maintaining the image of regional heads in the Regional Secretariat of JembranaDistrict had been going well, as seen from the indicators: Reception / hearing(domestic and foreign) was carried out in accordance with the specified standards.Guest visits (domestic and foreign) are carried out in accordance with applicableguidelines. Travel to the region / Overseas is carried out in accordance with specifiedguidelines. Meeting / session arrangements are well implemented. The holding of areception / banquet has been carried out well. The implementation of the ceremoniesis in accordance with the established rules. With the implementation of the duties andfunctions of the Public Relations and Protocol section, the image of the regional headcan be maintained properly, as seen from the indicators: Personality of the regionalhead increases with the implementation of public relations and protocol activitiesproperly. Reputation of Jembrana Regency has improved the implementation ofpublic relations and procolo activities. The value of Jembrana Regency increases withthe implementation of public relations and procolo activities properly. Identity or selfcan be seen by the implementation of public relations and protocol activities well.